2013
DOI: 10.1007/s12178-013-9185-8
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon ruptures

Abstract: The incidence of acute Achilles tendon ruptures is on the rise. This is thought to be due to the increasing number of middle-aged persons participating in athletic and/or strenuous activity. Ruptures of the Achilles tendon can be severely debilitating, with deficits seen years after the initial incident. Also, these injuries can have substantial socioeconomic impacts regardless of the treatment selected. Debate continues over the optimal treatment of Achilles tendon ruptures, especially the argument whether to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 88 publications
0
29
0
3
Order By: Relevance
“…Five out of six patients needed a small size split thickness skin graft at the donor site after a mean time of 7.1 days (range 7-9) of vacuum therapy to improve the granulation tissue and reduce the cosmetic impact on the forearm. DASH score values relating to the donor extremity resulted with a mean value of 8.0 points (range [3][4][5][6][7][8][9][10][11][12][13][14][15] with no significant functional impairment complained by patients. The MRI study at 8 months FU showed a nearly normal shape of the reconstructed tendon without interruptions, and the fusion between the two segments of FCR reaching in size the original Achilles tendon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five out of six patients needed a small size split thickness skin graft at the donor site after a mean time of 7.1 days (range 7-9) of vacuum therapy to improve the granulation tissue and reduce the cosmetic impact on the forearm. DASH score values relating to the donor extremity resulted with a mean value of 8.0 points (range [3][4][5][6][7][8][9][10][11][12][13][14][15] with no significant functional impairment complained by patients. The MRI study at 8 months FU showed a nearly normal shape of the reconstructed tendon without interruptions, and the fusion between the two segments of FCR reaching in size the original Achilles tendon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of acute Achilles tendon ruptures is increasing, probably following the arising diffusion of high demanding sports among inadequately trained middle-aged persons. [1][2][3] The open surgical repair of the tendon represents the gold standard; however, it is associated with significant rates of complications. 4 The most common complication is the wound dehiscence, which may be followed by infection, skin necrosis, exposure, and eventually necrosis of Achilles tendon.…”
mentioning
confidence: 99%
“…Patients typically refer to a “snap” followed by immediate onset of pain in the back of their lower leg and ankle. A functional limitation is usually experienced while walking and pointing the injured foot downward or while standing on the toes on the affected side 11 , 12 . Local swelling and a palpable defect proximal to the calcaneal insertion of the Achilles tendon may be detected on physical examination 11 , 12 ; dynamic clinical tests, such as the calf squeeze test, are also helpful 13 – 15 …”
Section: B‐mode Evaluation Of Achilles Tendons After Complete Rupturementioning
confidence: 99%
“…While not all injuries require surgical intervention, many classes of these injuries, such as rotator cuff and Achilles tendon tears, together account for more than 100,000 surgeries per year in the USA (Pedowitz and Kirwan, 2013; Vitale et al , 2007) and can show wide ranges of re-failure rates based on patient demographics (Galatz et al , 2006). Generally, tendon and ligament defects display poor intrinsic healing properties, requiring surgical intervention and result in fibrous scar tissue formation with misaligned extracellular matrix (ECM) and inferior mechanical properties, leading to high rates of injury recurrence (James et al , 2008; Liu et al , 2008; Xu and Murrell, 2008).…”
Section: Introductionmentioning
confidence: 99%